2022
DOI: 10.3390/app12147044
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Reducing Flow-Induced Cavity Resonance with a Narrowband Active Noise Control System

Abstract: In this paper, active control of flow-induced cavity resonance noise is addressed. A hybrid numerical method is presented to predict the resonance frequency and, instead of traditional active flow control, a narrowband active noise control system is utilized to suppress the resonance. A duct system is built up at low Mach numbers and experiments are carried out to validate the proposed methods. The results have shown that the resonance frequency could be predicted with 1.5% errors and the flow-induced narrowba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The simulations assisted in experimental measurements and verification. An et al [18] constructed an experimental platform to test and analyze cavity resonance noise caused by airflow, and a narrow-band active noise control system was utilized to mitigate cavity resonance noise. Results indicated that the active control system achieved a significant global attenuation of over 10 dB at the fundamental resonance frequency.…”
mentioning
confidence: 99%
“…The simulations assisted in experimental measurements and verification. An et al [18] constructed an experimental platform to test and analyze cavity resonance noise caused by airflow, and a narrow-band active noise control system was utilized to mitigate cavity resonance noise. Results indicated that the active control system achieved a significant global attenuation of over 10 dB at the fundamental resonance frequency.…”
mentioning
confidence: 99%